Emergence of listener responses after intraverbal teaching in a boy with autism - Silva, Elaine de Carvalho; Caixeta, Luiza Magalhães; Elias, Nassim Chamel (Perspectivas em Análise do Comportamento, 2020)
The literature has indicated that interventions that use the principles of Applied Behavior Analysis have produced promising results for addressing language skill deficits presented by children with Autism Spectrum Disorder (ASD). Considering that the difficulties of communication impair the quality of life of these children, it is justified the teaching of speaker (expressive language) and listener (receptive language) repertoires. Since these repertoires are functionally independent, the present study used Multiple Exemplar Instruction procedures to promote interdependence of the teaching of intraverbal responses (“Which Hand Is This?” - answer: “Right”) in the emergence of listener responses (“Show your right hand”). The objective was to verify the effects of teaching intraverbal responses of saying right or left for questions regarding the side of a body part (speaker repertoire) on the emergence of listener responses involving body parts (arms, hands, ears and legs) and spatial relationships of right and left in a six-year-old verbal boy with ASD. It was also verified the generalization of these relations to objects in the environment. The results indicated that the training of intraverbal responses prompted follow instruction listener responses to the participant, which confirms one of the teaching routes described in the literature (speaker-listener).